Utilization of interactive e-flipbook media oriented toward contextual approaches to learning in elementary schools - Aprilia, Tika; Djono, Djono; A'isyah, Amma (Jurnal Inovasi Teknologi Pendidikan, 2024)
An educator is required to continue to make updates in the learning process carried out, especially in learning media innovations that can support face-to-face and online learning. This study aims to determine the results of the feasibility analysis of interactive e-flipbook media oriented toward contextual approaches to science learning in elementary schools. This research uses a research and development approach, especially the design of the ADDIE. The subjects of the study were grade V students of an Elementary School in Surakarta. Data collection techniques include questionnaires and interviews. Data analysis is done using descriptive analysis. The results showed that the results of media expert validation obtained an average score of 4.38 in the very good category, and material expert validation obtained an average score of 4.59 in the very good category. Then the results of student responses to interactive e-flipbook products at the time of the initial trial, which included a one-to-one trial, obtained an average score of 3.54 included in the very good criteria; a small group trial obtained an average score of 3.37 included in the good criteria; and a field trial obtained an average score of 3.21 included in the good criteria. In addition, the results of the t-test at the field trial stage show that the value of probability or sig. (2-tailed) which is 0.000 < 0.05 and the coefficient = 4.688 greater than the coefficient value ttab = 2.018 then H0 is rejected meaning that there is an average difference in students' critical thinking ability scores between the experimental class and the control class at the field trial stage. The average post-test score in the experimental class was 83.45 and the average post-test score in the control class was 75.68. The average difference is 7.773. Thus, interactive e-flipbook media oriented towards contextual approaches is said to be feasible and can be used in science learning in elementary schools.